Two Novel Variants in Genes of Arrhythmogenic Right Ventricular Cardiomyopathy – a Case Report - Gabartaitė, Dovilė; Jančauskaitė, Dovilė; Mikštienė, Violeta; Preikšaitienė, Eglė; Norvilas, Rimvydas; Valevičienė, Nomeda; Marinskis, Germanas; Aidietis, Audrius; Barysienė, Jūratė (Acta medica Lituanica, 2021)
Background. Arrhythmogenic right ventricular cardiomyopathy (ARVC) is a heritable cardiomyopathy, characterized by fibrofatty replacement of myocytes in the right ventricular, left ventricular or both ventricles. It is caused by pathogenic variants of genes encoding desmosomal (JUP, DSP, PKP2, DSG2, DSC2) and non-desmosomal proteins, and is one of the most common causes of sudden cardiac death in young athletes. Therefore, early identification, correct prevention and treatment can prevent adverse outcomes.Case report. Our case presents a 65-years-old man with recurrent ventricular tachycardia. The ischemic cause was the first to rule out. Echocardiography revealed right ventricular structural and functional abnormalities. After suspicion of ARVC, magnetic resonance imaging was performed showing reduced right ventricular ejection fraction with local aneurysms, structural changes ir the right and left myocardium. Subsequently performed genetic testing identified a novel ARVC likely pathogenic variant in DSC2 gene and variant of uncertain significance in RYR2 gene.Conclusions. Diagnostic evaluation of ARVC is challenging and requires multidisciplinary team collaboration. Further functional tests for elucidation of the clinical significance of the two novel variants of ARVC-associated genes could be suggested.
Keywords: arrhythmogenic right ventricular cardiomyopathy; ventricular arrhythmias; desmosomal mutations